Just as they are (Journal of Parents and Teachers, 2025)
The article emphasizes the importance of allowing children to be themselves; that is, accepting their virtues and embracing their flaws to help them develop and become the best version of themselves. Additionally, it includes a story about Pedro Petrov and a recommendation of books to help students work on these aspects.
Keywords: children; acceptance; development; books